Role of neuroimmunomodulation by vagus nerve stimulation in rheumatoid arthritis: Are we heading towards a drug-free era? - Prasan Deep Rath; Swetal Pandey; Rahul Bisaralli (Indian Journal of Rheumatology)
Progressive clinical research in the field of neuroimmunomodulation has formed a base for the development of a new therapeutic paradigm for various inflammatory diseases, including rheumatoid arthritis (RA). One of the most common mechanisms is electrical vagus nerve stimulation of inflammation. The role of the vagal nerves in activation of various immune responses through preclinical and clinical evidence has established its role in assisting the control of inflammation and improving survival in the infectious and inflammatory disorders through efferent as well as afferent vagal pathways that regulate the peripheral inflammation via the central nervous system. Another mechanism is the neural inflammatory reflex that regulates innate and adaptive immune responses and also inhibits the production of a vital inflammatory therapeutic target molecule, known as tumor necrosis factor, for RA. This review discusses the multifactorial and multidimensional interactions between neurons and immune cells, the mechanisms of the nervous system which are responsible for the regulation of inflammation, the impact of cholinergic pathways on inflammation, and the evidence supporting the role of various bioelectronic devices in vagus nerve stimulation.